If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 1) + -4(x + -13) = 2 Reorder the terms: 2(1 + 3x) + -4(x + -13) = 2 (1 * 2 + 3x * 2) + -4(x + -13) = 2 (2 + 6x) + -4(x + -13) = 2 Reorder the terms: 2 + 6x + -4(-13 + x) = 2 2 + 6x + (-13 * -4 + x * -4) = 2 2 + 6x + (52 + -4x) = 2 Reorder the terms: 2 + 52 + 6x + -4x = 2 Combine like terms: 2 + 52 = 54 54 + 6x + -4x = 2 Combine like terms: 6x + -4x = 2x 54 + 2x = 2 Solving 54 + 2x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-54' to each side of the equation. 54 + -54 + 2x = 2 + -54 Combine like terms: 54 + -54 = 0 0 + 2x = 2 + -54 2x = 2 + -54 Combine like terms: 2 + -54 = -52 2x = -52 Divide each side by '2'. x = -26 Simplifying x = -26
| 20(-1)=19-2(-1) | | X+1.5=17 | | 25-2x=3x+10 | | (3+x)/5=(2x-9)/4 | | x^2+x-26=0 | | z^2+(3-2i)z+3-3i=0 | | 200-3X=42x+15 | | x+8y(x)-y=3y+7 | | 5x+10x=-65-10x | | 2x^2+22x+20= | | 5x-4=2(1-2x) | | 29.99+0.05(x-100)=39.99+0.03(x-200) | | 171-4x=6x-21 | | x=25/4+6.25+23/4+6.75+13/265.75+25/4+6.50 | | 4x+4x=25/4+6.25+23/4+6.75+13/265.75+25/4+6.50 | | 5x+22=7x-6 | | 2x+12=48-26 | | 3x+6-10=2x-2-6+10 | | 7x+30=4x+81 | | 7x+6x+5x=162 | | 140-7x=29x+20 | | 6x+58=11x+3 | | 162-6x=12x+18 | | 10-7x=60-21x | | x+x+1=x+4 | | x^2+4n-165=0 | | 3y-42=0 | | (64x^2-240x+120)+(21x^2-140x+70)=0 | | 87-6x=9x+22 | | 5y-3=4y+1 | | 16m^2-9n^2/4m+3n | | 5x-1=x-81 |